Over a million students use our free study notes to help them with their homework
5x-2=3x+11
Move the (-2) to the right handside. As it crosses over the (-) becomes a (+)
5x=3x + (11+2)
Move the (+3x) to the left handside. As it crosses over the (-) becomes a (+)
To make x the subject we want to try to get all the x's on one side of the equals sign! Firstly to get rid of the fraction we multiply both sides by 2, giving 3x+y= 2(x+z). We then expand the brackets on ...
i. A surd is an irrational number i.e. a non-whole number that can be represented as a square root, cube root etc.
ii. If the area of the square shape is 50cm^2, then we know that the length multip...
I know at first a lot of the formulae or techniques you use in maths may at first seem pointless, especially if you’re not planning on going into a scientific or mathematical field, but a lot of the thing...
rearrange equation (a) to be: y = 6 + 2x. Substitute this into equation (b) to get: (6 + 2x) + 2x = 0
rearrange this to get: 6 + 4x = 0. Simplify to get x = -(6/4). Get the val...
←
594
595
596
597
598
→
Internet Safety
Payment Security
Cyber
Essentials